Evaluation of the Rhythmic Arts Project, a Multi-Modal Rhythm-Based Perception and Action Intervention, in a School-Based Setting in Children with Autism Spectrum Disorders - Smith, Beth A.; Tuduri, Eddie; Mostovoy, Emily; Pannell, Denise; Landon, Chris (Journal of the American Academy of Special Education Professionals, 2019)
The Rhythmic Arts Project (TRAP) curriculum integrates visual, tactile, auditory and speech experiences through rhythmic drumming actions to address life skills. We evaluated life skills before and after participation in TRAP in a school-based setting in children with Autism Spectrum Disorders (ASD). Participants were 23 children in grades 6-12 in a special education program for students with ASD. We administered the Pediatric Evaluation of Disability Index Computer Adaptive Test (PEDI-CAT) before and after they participated TRAP. Children showed significant increases in participation in daily activities, mobility status, cognitive and social skills, and responsibility after participation in TRAP. We did not have a comparison or control group, however we used a repeated baseline design to support that changes were generally not observed over the summer when children were not participating in TRAP. Our results represent a first step in evaluating the effectiveness of TRAP by systematically measuring changes in life skills.